Conversion Therapy: Recognizing and Recentering the White Christian Nationalist Settler Origins - McNorton, Campbell (Kansas State University. Dept. of Social Transormation Studies., 2023)
This is my final research project for GWSS 405: Social Movements and Resistance. For this project, I decided that I wanted to research LGBTQ conversion therapy and the origins of the practice. With this research, I began to see and then examine the connection between modern day conversion therapy practices and Indigenous residential schools that were run in North America. In the paper I argue that conversion therapy is based in white colonial violence that upholds capitalism, white supremacy and settler colonial violence. However, despite the history of settler violence that is entwined with conversion therapy, most anti-conversion therapy activism centers white gay young men. So, instead of centering the normative white subject, I call for an alternate framework to be utilized in discussions surrounding conversion therapy-- an anti-colonial, anti-racist intersectional understanding of the settler colonial foundation. With this framework, I aim to work toward coalitions that work together against cis-hetero settler violence that continues to impact conversion therapy.
Kirmser Undergraduate Research Award - Individual Non-Freshman category, honorable mention
Keywords: Conversion Therapy; White Christian Nationalist Settlers; LGBTQ; Settler Colonial Violence; Indigenous Residential Schools